2008
DOI: 10.1371/journal.pone.0002939
|View full text |Cite
|
Sign up to set email alerts
|

A Common Anterior Insula Representation of Disgust Observation, Experience and Imagination Shows Divergent Functional Connectivity Pathways

Abstract: Similar brain regions are involved when we imagine, observe and execute an action. Is the same true for emotions? Here, the same subjects were scanned while they (a) experience, (b) view someone else experiencing and (c) imagine experiencing gustatory emotions (through script-driven imagery). Capitalizing on the fact that disgust is repeatedly inducible within the scanner environment, we scanned the same participants while they (a) view actors taste the content of a cup and look disgusted (b) tasted unpleasant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
194
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(220 citation statements)
references
References 56 publications
20
194
0
1
Order By: Relevance
“…These FTD findings may reflect a basic role for the VENs, fork cells, and related circuitry in the control of appetite. The anterior insula/FI is activated when subjects view facial expressions of disgust (Phillips et al 1997;Jabbi et al 2008). Disgust (literally, bad taste) links appetite control and social feedback, which we believe are two key functions of these circuits.…”
Section: Nmb Expression In the Vensmentioning
confidence: 89%
See 1 more Smart Citation
“…These FTD findings may reflect a basic role for the VENs, fork cells, and related circuitry in the control of appetite. The anterior insula/FI is activated when subjects view facial expressions of disgust (Phillips et al 1997;Jabbi et al 2008). Disgust (literally, bad taste) links appetite control and social feedback, which we believe are two key functions of these circuits.…”
Section: Nmb Expression In the Vensmentioning
confidence: 89%
“…The region corresponding to FI on the right side is also activated when subjects scrutinize facial expressions to discern intentions (Baron-Cohen et al 1999). The integrative functioning of the lateral part of FI in response to negative feedback is illustrated in a series of experiments by Jabbi et al (2008) who elicited activity in this VEN-rich region through experiences involving disgust mediated by taste, by the observation of someone else responding to a disgusting taste, and by imagining a disgusting taste. (Note, however, that the activity observed in these experiments could also have arisen from the adjacent inferior frontal region.)…”
Section: Introductionmentioning
confidence: 99%
“…Further research has suggested that similar systems of shared representation of self and other exist for perception of pain (Bernhardt & Singer, 2012;Fitzgibbon, Giummarra, Georgiou-Karistianis, Enticott, & Bradshaw, 2010), touch (Keysers, Kaas, & Gazzola, 2010;Schaefer, Heinze, & Rotte, 2012) and emotional processing (Bastiaansen, Thioux, & Keysers, 2009;Jabbi, Bastiaansen, & Keysers, 2008). While there is still considerable debate about exactly how these shared activations contribute towards the understanding of others (see the following reviews for three distinct accounts: Cook, Bird, Catmur, Press, & Heyes, 2014;Gallese, 2007;Kilner, Friston, & Frith, 2007), the involvement of neural systems involved in representing the bodily self in social cognition is now well established.…”
Section: Prejudice and The Bodily Selfmentioning
confidence: 99%
“…However, the insula is very difficult to observe from a lateral view because of its anatomical position. The insula is the specific brain region that is responsible for disgust [69,70]. A meta-analysis of neuroimaging results on emotional processing revealed that the insula is also associated with threat-related emotions, such as fright [71,72].…”
Section: Insula and Cerebellummentioning
confidence: 99%